Influence of Temperature and pH Conditions on the Swelling Properties of Rice Straw Derived Cellulose Hydrogel - Vu, Tung Lam; Nguyen, Ngoc Mai (JST: Engineering And Technology For Sustainable Development, 2022)
Cellulose, one of the renewable and biodegradable polymers, has been extensively studied as a raw material for a newly and fully bio-based hydrogel. The synthesis of bio-hydrogel based on the dissolution of extracted cellulose from rice straw in tetrabutylphosphonium hydroxide (TBPH) solvent followed by the gelation using epichlorohydrin (ECH) crosslinkers. The success of the extraction of cellulose from rice straw was evaluated by characteristic peaks of cellulose in Fourier Transform Infrared Spectroscopy (FTIR) spectrum. The hydrogel formation mechanism was investigated in this article, as well as the evaluation of swelling properties under different temperature and pH conditions. As hydrogel exhibited thermal and pH sensitive behavior, the highest swelling capacity was found at pH 7.0 and 60 ºC. The characterization of hydrogel was examined by Fourier Transform Infrared Spectroscopy (FTIR) and thermal analysis (TGA), indicating that the rice straw derived cellulose hydrogel was cellulose type II, similar to others hydrogels. The morphology of extracted cellulose and hydrogel were investigated by Scanning Electron Microscope (SEM). The hydrogel exhibited porousity structure with very large pore size that surrounded by cellulose/ECH layers. The purity of the hydrogel was determined through the amount of water immersed in the hydrogel for one day by Liquid Nuclear Magnetic Resonance (NMR) for the residual TBPH determination.